Analisis Kinerja Keuangan Pemerintah Desa Rantau Karya Kabupaten Tanjung Jabung Timur Periode 2019-2021 - Ine Ardita Hartono; Iskandar Sam; Gandy Wahyu Maulana Zulma (Universitas Batanghari Jambi, 2023)
The purpose of this research is to analyze the financial performance of the Rantau Karya Village Government of East Tanjung Jabung Regency in 2019-2021. Village Government Financial Performance is an important indicator for evaluating the efficiency of financial management, transparency and accountability in the use of public resources. This research method uses a quantitative descriptive approach using financial data contained in the financial reports of the Rantau Karya Village Government during the period studied. The data used includes village receipts and expenditures, as well as significant village income and expenditure items. The results showed that the Financial Performance of the Rantau Karya Village Government could be categorized as very high based on the Village Financial Dependence Ratio, whereas the Effectiveness Ratio of Village Original Income showed ineffective performance, and the Village Spending Efficiency Ratio was categorized as less effective. It is hoped that this research can provide valuable insights for the village government, stakeholders, and society in general to improve village government financial management. The results of this study can also be a reference for local governments in formulating policies related to village financial management.